Fostering Economic Development Through Women's Leadership and Organizational Ambidexterity: A Path to Superior Business Performance - Laily, Nur; Bambang Mahargiono , Pontjo; Djuraidi, Achmad; Sejati, Agung; Dwi Jayanti, Risma (International Journal of Economics Development Research (IJEDR), 2025)
In the business world, organizational ambidexterity (OA) is becoming more and more important, particularly in women-led SMEs. The purpose of this study is to ascertain how organizational ambidexterity mediates the impact of female leadership on the financial performance of women-led SMEs. The study's population consisted of 190 female SME owners in Indonesia, and SEM PLS was used to analyze the data. The results of the study demonstrate that OA can mediate the impact of female leadership on business success, that OA influences OA, and that both OA and female leadership have an impact on business performance. The association between female leadership and the business success of female SME actors is strengthened by organizational ambidexterity, which functions as an intervening variable. Female SME leaders can boost competitiveness and sustainable business growth by utilizing current resources and exploring new opportunities. As a result, the creation of OA is one of the most important tactics for assisting the advancement of women-led SMEs in Indonesia.